Endurance training increases ventricular refractoriness and wavelength of the cardiac impulse without participation of parasympathetic postganglionic neurons. A study in isolated rabbit heart. (14th October 2021) - Rodrigo-Garcia, A; Such-Miquel, L; Parra, G; Calvo, C J; Arias-Mutis, O J; Lozano, W M; Such, L; Alberola, A; Chorro, F J; Zarzoso, M
Abstract: Background: Endurance physical training plays a protective role in against ventricular fibrillation (VF), but the exact underlying mechanisms are not completely understood. It is well-known that modifications in myocardial ventricular properties such as refractoriness, conduction velocity and wavelength are key in the initiation and maintenance of VF; furthermore, vagus nerve stimulation has prophylactic effects on malignant arrhythmias and VF. On the other hand, parasympathetic nervous system activity is increased in trained individuals, which in turn affects different ventricular electrophysiological properties. We hypothesized that physical training increases conduction velocity and wavelength, and that these changes are mediated by myocardial cholinergic neurons. Methods: To test this hypothesis, ten rabbits were submitted to a six-week endurance training protocol and twenty controls were not trained (divided in control group, n=10 and sham group n=10). After training, rabbits were euthanized and their hearts excised, isolated and perfused in a Langendorff system. A pacing electrode and a plaque with 240 recoding electrodes acquiring at 1 KHz were positioned on the left ventricle (LV). Extraestimulus test using four different pacing cycle lengths (90% basal cycle length, 250, 200 and 150 ms) was performed before and after atropine (1μM, control and trained groups) or vehicle (tyrode, sham group) infusion. We studied 1) LV effective refractory period (ERP), 2) LV functional refractory period (FRP), 3) LV conduction velocity (CV), and 4) LV wavelength, determined as LV FRP x CV. Factorial ANOVA (mixed model) was used for statistical analysis (p<0.05). Results: Before parasympathetic blockade, LV FRP increased in trained animals (Figure, B) whereas no difference was found in LV CV between trained and control animals at any pacing cycle length (Figure, A). In consequence, LV wavelength increased in trained animals (Figure, C). There were no changes in LV ERP, FRP, CV and wavelength when comparisons were made within groups before and after atropine infusion. In sham animals, vehicle infusion or time-course of the experiment did not modify LV FRP, ERP, CV and wavelength. Conclusion: Physical training increases LV wavelength, which can be one electrophysiological mechanism by which endurance training could protect against VF. Since modifications of ventricular refractoriness and wavelength do not seem dependent of intrinsic parasympathetic nervous system activity, other intrinsic mechanisms could be implied and warrant further research. FUNDunding Acknowledgement: Type of funding sources: Public grant(s) – National budget only. Main funding source(s): Instituto de Salud Carlos III, Generalitat Valenciana